Al-Kashi and access to the arithmetic & astronomy - Rasheed, Aous Naji; Kabbashi, Nassereldeen Ahmed (IIUM Press, 2011)
Muslim scientists played a significant role in the history of science. There were hundreds of notable Muslim scientists who made great contributions to the society. Muslims carried the torch of learning for five hundred years; from 8th century to 13th Century. It is worthy to mention that engineering has an impact to develop human life especially when we know that this includes verious fields such as mathematic, physics, astronomic, architecture, optic and other types which have relation with this word. So the objective of this chapter is to focus the light on Muslim scientists' contributions in this science. Also the significance ofthis chapter is to research the contributions of Al-Kashi in astronomical and mathematical issues. The methodology is purely on library based study using books, journals and other relevant sources. In this chapter we will discuss Ghiathudin Al-Kashi. He was born in 1380 in Kashan, a town modem in Iran.